2014
DOI: 10.1007/s12160-014-9645-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Qigong/Tai Chi Easy on Cancer-Related Fatigue in Breast Cancer Survivors

Abstract: Background Many breast cancer survivors experience fatigue, mood, and sleep disturbances. Purpose To compare a Meditative Movement practice, Qigong/Tai Chi Easy (QG/TCE), with sham Qigong (SQG), testing effects of meditation/breath aspects of QG/TCE on breast cancer survivors' persistent fatigue and other symptoms. Methods A double-blind, randomized controlled trial tested 12-weeks of QG/TCE versus SQG on fatigue, depression and sleep among 87 post-menopausal, fatigued breast cancer survivors, Stage 0-III,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
203
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(213 citation statements)
references
References 66 publications
4
203
0
6
Order By: Relevance
“…This study was intentionally designed as a cross-over study, however due to the high drop-out rate before and after the cross-over, the study was discontinued. Previous martial arts studies have also reported relatively high drop-out rates, suggesting that these type of interventions are not suitable for everyone (17,16). This applies to our study as well.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…This study was intentionally designed as a cross-over study, however due to the high drop-out rate before and after the cross-over, the study was discontinued. Previous martial arts studies have also reported relatively high drop-out rates, suggesting that these type of interventions are not suitable for everyone (17,16). This applies to our study as well.…”
Section: Discussionsupporting
confidence: 63%
“…When designing this randomized controlled two-armed intervention study we hypothesized that a holistic training program which is based on "Kyusho Jitsu" martial arts and lasts for 24 weeks is feasible and will have a positive effect experienced side effect, were also supported (16,23). Further, it may lead to improvements in overall quality of life (24) and psychological well-being (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study conducted by Larkey et al [5] aimed to examine the differences between these three components together versus physical exercise alone for the clinical beneficial effects of Qigong using a double-blind, randomized controlled trial over 12 weeks of Qigong /TCE versus Sham Qigong on fatigue, depression, and sleep among 87 postmenopausal, fatigued breast cancer survivors, stages 0-III, age 40-75. The researchers concluded that gentle exercise -that is, simply getting breast cancer survivors moving -may be beneficial in reducing a number of symptoms and boosting well-being of breast cancer survivors (depression and sleep quality).…”
Section: Introductionmentioning
confidence: 99%